Regulating dual temperature- and pH-responsibility constructed from core-shell mesoporous hybrid silica (P(NIPAM-co-AA)@BMMs) via adjusting AA incorporation onto NIPAM. Issue 8 (24th May 2019) - Jin, Xiaoqi; Wang, Qian; Sun, Jihong; Panezai, Hamida; Bai, Shiyang; Wu, Xia
Abstract: The mesoporous hybrid silicas (P@BMMs) with core-shell structure were successfully synthesized via seed polymerization method using bimodal mesoporous silica materials (BMMs) as core and dual pH- and temperature-responsive poly( N -isopropylacryl-acrylamide)-co-poly(acrylic acid) (P(NIPAM-co-AA)) copolymer as shell. Meanwhile, the obtained P@BMMs were physicochemically and morphologically characterized via X-ray diffraction, N2 adsorption-desorption isotherms, scanning electron microscopy, transmission electron microscopy, Fourier transform infrared, ultraviolet visible diffused reflection spectrum, small angle X-ray scattering (SAXS), dynamic light scattering, and thermogravimetric analysis techniques. The results indicated that P(NIPAM-co-AA) was successfully coated onto the mesoporous surface of used BMMs, while the uniform mesoporous structure of obtained P@BMMs was still preserved. Using ibuprofen (IBU) as a model drug, the influence of the P(NIPAM-co-AA) shell on the release kinetics of IBU was explored, and its performances elucidated that the P@BMMs nanoparticles presented an apparent thermo/pH-responsive properties, which could be regulated via adjusting mass ratio of AA to NIPAM, and their IBU-release kinetic profiles were favorable to Korsmeyer-Peppas model. Specially, SAXS patterns were employed to evaluate the fractal evolution of P@BMMs along with releasing time, showing the decline tendency for mass fractal value from 2.89 to 2.56 during the release time of 0.25–24 h. Graphical Abstract: